Psychoanalysis and literature: Elfriede Jelinek or the woman at the sidelines - Vargas García, Kelly (Revista de Letras, 2019)
This article aims to reveal what the writer Elfriede Jelinek teaches in her novel “Lust” about the feminine and the woman in psychoanalysis. To explain this purpose it involves three moments: first, the method that Sigmund Freud and Jacques Lacan suggest to approach literature; second, the psychoanalytic notions of prehistory to the Oedipus complex and the woman are examined, in articulation with the premise “Sidelined” in the work of Jelinek; and finally, the novel “Lust” is analyzed which it emphasizes in the dimension of an act that enables the emergence of the feminine.